Magnesium: pathophysiological mechanisms and potential therapeutic roles in intracerebral hemorrhage - Chang, Jason J. (Neural Regen Res, 2019)
Intracerebral hemorrhage (ICH) remains the second-most common form of stroke with high morbidity and mortality. ICH can be divided into two pathophysiological stages: an acute primary phase, including hematoma volume expansion, and a subacute secondary phase consisting of blood-brain barrier disruption and perihematomal edema expansion. To date, all major trials for ICH have targeted the primary phase with therapies designed to reduce hematoma expansion through blood pressure control, surgical evacuation, and hemostasis. However, none of these trials has resulted in improved clinical outcomes. Magnesium is a ubiquitous element that also plays roles in vasodilation, hemostasis, and blood-brain barrier preservation. Animal models have highlighted potential therapeutic roles for magnesium in neurological diseases specifically targeting these pathophysiological mechanisms. Retrospective studies have also demonstrated inverse associations between admission magnesium levels and hematoma volume, hematoma expansion, and clinical outcome in patients with ICH. These associations, coupled with the multifactorial role of magnesium that targets both primary and secondary phases of ICH, suggest that magnesium may be a viable target of study in future ICH studies.